HUBUNGAN TINGKAT PENGETAHUAN IBU DAN DUKUNGAN SUAMI DENGAN PENGGUNAAN KONTRASEPSI IUD (INTRA UTERINE DEVICE) PADA AKSEPTOR KB DI PUSKESMAS LUBUK BUAYA - Hendri Devita; Filya Destika; Putri Engla Pasalina; Novi Maya Sari (Poltekkes Kemenkes Medan, 2023)
Based on data obtained from the Lubuk Buaya Health Center, Padang City in 2020 the number of mothers was 14,534 people with the number of active family planning participants as many as 10,639 people, while those using the IUD at the Lubuk crocodile health center were only 345 people (3.2%) and ranked number 11 using the IUD. IUD contraception. The rest still use condoms, pills, and injections because the mother's knowledge about IUD contraception and support from her husband is still lacking, so IUD contraception is decreasing. The purpose of this study was to determine whether there was a relationship between the level of mother's knowledge and husband's support with the use of IUD contraception on family planning acceptors at the Lubuk Buaya Health Center in 2022. This type of research was an Analytical Survey with a Cross Sectional approach where the Dependent and Independent variables were carried out at the same time. This study was conducted from January to April 2022. The population was 102 people with a sample of 34 respondents. Sampling by accidental sampling, with a total of 34 respondents. The results showed that there was a significant relationship between the mother's level of knowledge and the use of IUD contraception p value 0.049 (<0.05), there was a significant relationship between husband's support and the use of IUD contraception p value 0.004 (<0.05).